Risk of contrast-induced nephropathy in patients undergoing complex percutaneous coronary intervention. (1st September 2019) - Azzalini, Lorenzo; Poletti, Enrico; Lombardo, Francesca; Laricchia, Alessandra; Beneduce, Alessandro; Moscardelli, Silvia; Bellini, Barbara; Maccagni, Davide; Cappelletti, Alberto; Ancona, Marco B.; Carlino, Mauro; Chieffo, Alaide; et al.
Abstract: Background: Complex percutaneous coronary intervention (PCI) is associated with increased procedural challenges and high contrast load. We aimed to evaluate the association between complex PCI and contrast-induced nephropathy (CIN). Methods: This single-center retrospective study included all-comers undergoing PCI between January 2012 and December 2016. Complex PCI was defined as a procedure with ≥1 of the following characteristics: 3 vessels treated, ≥3 stents implanted, two-stent bifurcation intervention, total stent length >60 mm, PCI on a chronic total occlusion, saphenous vein graft, or left main, protected PCI, use of rotational/laser atherectomy. CIN was defined as an increase in post-PCI creatinine of ≥0.3 mg/dl or ≥50% from baseline. Results: We included 2660 patients ( n = 1128 complex PCI, n = 1532 non-complex PCI). Complex PCI patients tended to be older, and had higher cardiovascular comorbidity and Mehran CIN risk score. They also had a higher prevalence of type B2/C lesions and need for mechanical circulatory support, and received a higher mean contrast volume (284 ± 137 vs. 189 ± 90 ml, p < 0.001). CIN incidence was similar in complex vs. non-complex PCI patients (12.1% vs. 11.5%, p = 0.63), as was the need for in-hospital dialysis (0.5% vs. 0.2%, p = 0.25). Upon multivariable adjustment, age, female sex, diabetes, ejection fraction, periprocedural hypotension, presentation with acute coronary syndrome, and contrast volume were independently associated with CIN, while complex PCI was not. Conclusions: Complex PCI is not associated with an increased risk of CIN in all-comers. Further studies should confirm our findings and investigate novel effective strategies to decrease the risk of this serious complication. Highlights: Complex PCI is associated with procedural challenges and higher contrast volumes. Complex PCI might be linked to a higher risk for contrast-induced nephropathy. CIN incidence was similar in complex vs. non-complex PCI (12.1% vs. 11.5%, p = 0.63). Upon multivariable adjustment complex PCI was not independently associated with CIN.